DO LEARNERS CONNECT SOCIOPHONETIC VARIATION WITH REGIONAL AND SOCIAL CHARACTERISTICS? - Chappell, Whitney; Kanwit, Matthew (Studies in second language acquisition, 2022)
Learners must develop the ability to perceive linguistic and social meaning in their second language (L2) to interact effectively, but relatively little is known about how learners link social meaning to a single phonetic variable. Using a matched-guise test targeting coda /s/ (realized as [s] or debuccalized [h]), we explore whether L2 Spanish learners identify native speakers’ social characteristics based on phonetic variants. Our results indicate that advanced learners were more sensitive to sociophonetic information; advanced listeners who had completed a phonetics course were significantly more likely to categorize /s/ reducers as Caribbean and those who had studied abroad in aspirating regions recognized a relationship between coda /s/ and status. To account for the complex interplay among proficiency, explicit instruction, and dialectal exposure in the development of L2 sociophonetic perception, we suggest the union of the L2 Linguistic Perception Model with exemplar models of phonological representation and indexical meaning.